THE CONSTRUCTION OF MUSLIM GEN-Z SPIRITUALITY THROUGH SOCIAL MEDIA AND MOSQUE COMMUNITIES - Muammar Zulfiqri; Alip Nuryanto (Universitas Islam Depok, 2025)
This study investigates how Muslim Generation Z (born 1997–2012) constructs their spirituality through the dual dynamics of social media engagement and mosque community participation in the contemporary digital era. Employing a systematic literature review methodology guided by the PRISMA framework and incorporating thematic analysis of 48 peer-reviewed articles published between 2018 and 2026, the study maps the emerging landscape of digital Islamic piety and examines how online platforms particularly Instagram, TikTok, YouTube, and Twitter/X intersect with physical community institutions such as mosque youth organizations (remaja masjid) in shaping Gen-Z Muslim spiritual identity. The findings reveal three primary mechanisms through which Gen-Z Muslim spirituality is constructed: (1) algorithmic exposure and voluntary content consumption on social media platforms, which democratize religious authority and generate new forms of